Taxonomy and Phylogeny of Fomitiporia bharatavarsa , an Undescribed Species From Tamil Nadu, Southern India - Elangovan Arumugam; Malarvizhi Kaliyaperumal (New Zealand Journal of Botany, 2026)
A new species of Fomitiporia is illustrated and described based on taxonomic studies and phylogenetic analyses. Fomitiporia bharatavarsa is characterized by perennial, resupinate basidiomes, circular pores (4–7 per mm), dimitic hyphal system, presence of hymenial setae, cystidioles, abundant rhomboid crystals, and thick‐walled broadly ellipsoid‐to‐subglobose basidiospores measuring 5.5–6.3 × 5.2–5.5 µm. Phylogenetic analyses inferred from ITS and nLSU rDNA sequences revealed that F. bharatavarsa represents a new lineage and formed a sister group to F. aethiopica , F. carpinea , F. erecta , F. mediterranea , F. pseudopunctata , F. punicata , and F. tsitsikamensis . Our study represents pioneering report on the new species of Fomitiporia , which has been described and discussed with allied taxa in taxonomic and phylogenetic aspects.